Increased insecticidal activity by photoprotection of microencapsulated spinosad in a dry phagostimulant formulation against Drosophila suzukii. (May 2022) - Pérez-Landa, Irving D.; Lasa, Rodrigo; Gonzalez-Chi, P.I.; Bonilla-Landa, Israel; Olivares-Romero, José L.; Barrera-Méndez, Felipe
Abstract: The spotted wing drosophila (SWD) ( Drosophila suzukii ), originally from Asia, has spread across Europe and North America since 2008, threatening soft fruit crops. Spinosad is widely used due to low toxicity to non-target organisms and proven lethality to SWD. This study aims to examine how to preserve the efficacy of spinosad under environmental conditions in the field. In this context, a dry phagostimulant formulation was prepared to contain spinosad biopolymeric microparticles based on chitosan and sodium lignosulfonate. LC50 (90.17 ppm ai) and LC90 (318 ppm ai) were determined, followed by choice tests that showed the phagostimulant with the microencapsulated spinosad improved results compared to the phagostimulant with unencapsulated spinosad. Laboratory bioassays showed that microencapsulation could extend the effectiveness of this bioinsecticide. The application of the formulation on strawberry leaves in the greenhouse was not as effective after 42 days compared to applications in a Petri dish. Our studies suggest that microencapsulated spinosad could be a useful compound in trapping devices since it offers an environmentally friendly option to control D. suzukii . Highlights: The spinosad microspheres toxicity in a dry phagostimulant formulation was evaluated. The encapsulation improved attraction avoiding repellence to the bioinsecticide. Biopolymers protect spinosad against photodegradation. Spinosad was harmful to D. suzukii adults for up to 42 days in a greenhouse. Baits combined with encapsulated bioinsecticides could be an option for pest control.